An exploration of the research framework for the coupling of farmland and rural residential land use transition under the perspective of spatial production - LI Jingjing, FENG Yingbin, GU Lei, LI Yue (Ziyuan Kexue)
[Objective] The exploration of feature identification, pattern judgment, and mechanism response in the coupling of farmland and rural residential land use transition is a key link in studying the complex correlation characteristics and multiple causal problems of land use transition, which is also a scientific problem that urgently needs to be solved in the land system. [Methods] This study utilized literature collection to categorize the development stage, characteristics, and pattern changes of the coupling of farmland and rural residential land use transition from the perspective of spatial production, systematically analyzed the influencing factors of the coupling of farmland and rural residential land use transition under spatial production, and attempted to construct a driving mechanism framework to explore the regulatory strategies and application directions. [Results] By analyzing the spatiotemporal and micro-characteristics of the coupling of farmland and rural residential land use transition from explicit and implicit perspectives, dividing the pattern by combining the types of natural resources, rural development, and functional changes, and considering the influencing factors of nature, society, economy, culture, and ecology as a whole system, a framework of the coupling mechanism of farmland and rural residential land use transition from a telecoupling perspective was explored and constructed, additionally, the ideas of regulatory strategies were proposed. Overall, the research framework of “feature identification - pattern judgment - mechanism response” for the coupling of farmland and rural residential land use transition from the perspective of spatial production was formed. [Conclusion] Future research on the coupling of farmland and rural residential land use transition needs to focus on the following aspects. Firstly, there is a need for quantitative measurement of implicit forms. Secondly, it is important to quantify the multiple nested relationships and effects among sending, receiving, and spillover systems under the perspective of telecoupling from the system viewpoint. Lastly, there is a need to explore the development path and regulation mode of land use transition for rural revitalization and agricultural and rural modernization.